Parametric study of free turbulent slurry jet: influence of particle size and particle concentration on the flow dynamics and thermal behavior of high-speed slurry jet - Nilesh Kumar Sharma; Satish Kumar Dewangan; Pankaj Kumar Gupta (Journal of Engineering and Applied Science, 2024)
Abstract A detailed computational investigation was conducted to explore the dynamics of high-speed free slurry jets, with a focus on how variations in abrasive size and concentration affect their behavior. The study yielded several significant observations: Firstly, it was observed that slurry jets containing larger particles exhibited notably higher average velocities, attributed to their inherent self-similar characteristics. Specifically, at the far field of the jet, slurry jets with larger particle sizes demonstrated a 15% increase in velocity compared to those with smaller particles. Additionally, an analysis of turbulent intensity revealed that beyond a certain axial distance (x/D = 10), turbulence levels progressively increased. However, intriguingly, for slurry jets with a high concentration (Co = 15%), there was a notable decrease (28%) in turbulent intensity compared to water jets, indicating a complex interplay between particle size and concentration. Secondly, the study found that as the concentration of particles in the slurry jet increased, there was a corresponding rise in the bulk temperature of the jet. This phenomenon was primarily attributed to the heightened thermal conductivity resulting from the increased density of particles in the water. Furthermore, an examination of the Nusselt number revealed interesting trends. While the Nusselt number exhibited a peak near the nozzle exit, indicative of enhanced heat transfer in this region, it showed a decremental trend along the axial direction of the jet, attributable to jet divergence. In summary, the computational analysis provided valuable insights into the behavior of high-speed slurry jets, highlighting the intricate relationships between abrasive size, concentration, velocity distribution, and thermal characteristics. These findings contribute to a deeper understanding of slurry jet dynamics and have significant implications for various industrial applications.